A proposed implementation and design of web-based property information system for Malaysian market / Mustaffa Kamal Mohd Nor, Mohamad Nizam Ayub and Foo Yuke Shean - Mohd Nor, Mustaffa Kamal; Ayub, Mohamad Nizam; Foo, Yuke Shean (2006)
Currently, some people are consuming a lot of time, cost and effort in seeking and buying a property for example a house. Potential house buyers usually approach the housing developers by visiting the sales offices to look for suitable house for their needs. But, it is not always easy. Looking and searching for information sometimes may be so tedious and difficult. Having the Internet available at our fingertips can provides the house buyers the convenience and more importantly can save time and their money. Therefore, this paper will discuss a web- based property Information System called Web House. This Web House is a Web-based housing Information system that provides information about new residential and housing projects. This information system is a database-driven computerized and Web-enabled system that provides information about housing projects such as house models, price ranges, specifications and descriptions of each house, etc. Web House applies the client-server architecture. The overall system development strategy of Web House is using the Waterfall Development Life Cycle Model with prototyping. The Web server of Web House is the Internet Information Server (IIS) running under the Window NT 4 Server operating system, whereas the database server is the SQL server. Active Server Pages (ASP) is the main programming language technology to develop the system based on the system requirements.